RELATIONSHIP BETWEEN FEEDING AND OVARIAN CYCLE IN SCHIZOTHORAX NIGER HECKEL AND BOTIA BIRDI CHAUDHRY - Malhotra, Y R (Indian Journal of Fisheries, 2011)
Miescher (1897) has shown that salmon go practically without food so longas they are in fresh water, being nourished by the large store of fat depositedwhen they were in the sea. Carr (1908, 1909) observed high percentages ofempty stomachs among specimens of Pleuronectes limanda, Hippoglossus limandoidesand Gadus merlangus during the winter months and he attributed this tolow temperature. Russel (1914) and Todd (1915) associated the empty stomachsof Pleuronectes platessa with the advent of spawning. Bigelow and Welsh (1924)working on Osmerus mordax, Pomolobus pseudoharengus and Alosa sapidissimastated that the cessation of feeding in fresh waters by these anadromou^ fishesis due to their spawning migrations. Homans and Vladykov (1954) have observefithat the haddock Melanogrammus aegilifinus ceases to take food during thespawning season, but feeds voraciously after termination of the spawning season,trying to regain the weight lost due to spawning.